Analisa Ruang Publik Koridor Jalan Ratulangi di Makassar - Haryanto Andi Halim; Abd. Azis Alimuddin (Universitas Muslim Indonesia, 2016)
The Ratulangi area in Makassar City was formerly a connecting road between the Tallo Kingdom in the North and the Gowa Kingdom in the South. This area still contains historical buildings and has become an environment for offices, trade, services, and commercial activities. The traffic in the Ratulangi area is quite busy, supported by relatively good road infrastructure, with a variety of vehicle types passing through. Consequently, the working hours in this area are very dense, while the urban elements and facilities in this area are still lacking and inadequate when viewed from the various urban activities occurring here. The purpose of this study is to analyze the presence of open space functions in the buildings along the road corridor, selecting several points based on building functions, open spaces, and their locations relative to Ratulangi Street. The study aims to identify the functions of buildings and the supporting activities that occur along the Ratulangi road corridor as a solution to the existing problems. This research utilizes the theories of circulation, pedestrian pathways, and activity support from Hamid Shirvani in his book The Urban Design Process. The author employs observation and documentation as data collection methods, while the data analysis method is qualitative phenomenological. The main issue focuses on the meaning and experiences of subjects in their daily lives, aiming to explain how objects and experiences are created with full meaning and communicated in everyday life, treating subjectivity as the research topic itself. This research is expected to provide benefits so that urban planning, particularly along road corridors, can be organized well according to urban element standards.